GREEN MARKETING STRATEGY: HUBUNGAN GREEN PERCEIVED VALUE DAN GREEN TRUST - ALAMSYAH, DONI PURNAMA (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2016)
Green Marketing Strategy has become the latest strategy for the company, especially for two-wheeled vehicles in Indonesia with innovative environmentally friendly products. It is interesting assessed as innovation in environmentally friendly products has not been applied in Indonesia. So the focus of research studies on the description and influence between the variables in the green perceived value and green trust of consumers for environmentally friendly products. Descriptive and verification combined with survey method in this research with 105 respondents, who are consumers of Honda brand vehicles by using simple linear regression analysis techniques. Results found a good overview on the green perceived green value and green trust. As well as the relationships and the influence of green perceived value to green trust. So to say precisely when companies in Indonesia has used a green marketing strategy in the competitive business. Given the good response to the innovation of products friendly to the environments. Keywords: green perceived value, green trust